# solve using an interval sign table?

a) 2(x+3)(x-1)(x-5)<=0

b) -3(x+4)(x-3)^3>0

### 2 Answers

- Wayne DeguManLv 74 weeks agoFavourite answer
a) x = -3, 1 and 5 are values that give zero

so, for x < -3, say -4 we get:

2(-4 + 3)(-4 - 1)(-4 - 5) = 2(-1)(-5)(-9) < 0

For -3 < x < 1, say 0 we get:

2(0 + 3)(0 - 1)(0 - 5) = 2(3)(-1)(-5) > 0

For 1 < x < 5, say 2 we have:

2(2 + 3)(2 - 1)(2 - 5) = 2(5)(1)(-3) < 0

And for x > 5, say 6 we have:

2(6 + 3)(6 - 1)(6 - 5) = 2(9)(5)(1) > 0

so, for x < -3 or when 1 < x < 5 we have < 0

Hence, for x ≤ -3 or when 1 ≤ x ≤ 5 we have ≤ 0

i.e. (-∞, -3] ∪ [1, 5]....using interval notation

:)>

- rotchmLv 74 weeks ago
Strange that you would ask for help for such elementary questions when in the past you have been doing much more advanced math than that!

Are you at least trying? Take your time to read the question and to understand what they want. Depending on the sighs of a, b & c, when is a*b*c positive? That is what they are basically asking.